Defining the content and structure of potential reserve officers for daily and combat activity - Медвідь, Ю. І. (Scientific notes of the pedagogical department, 2018)
Based upon the analysis of scientific works, the content of readiness of potential reserve officer for daily and combat activities has been defined as the personality manifestation formed by the purposeful  pedagogical impact on developing in a citizen the readiness to defend his/her Motherland, and to serve in military formations; and provides conformity of  his/her knowledge about the content and structure of daily and combat activities with the requirements to state of health and mind; the level of acquired competences for daily and combat activities with attained skills and needs; as well as the structure  of such readiness including  its motivational, functional and strong-willed components.